Part i
![\dfrac{2a-7}{6y} = \dfrac{3b-5}{2c}](https://tex.z-dn.net/?f=%20%5Cdfrac%7B2a-7%7D%7B6y%7D%20%3D%20%5Cdfrac%7B3b-5%7D%7B2c%7D)
![y = \dfrac{ 2c(2a-7)}{6(3b-5)} = \dfrac{c(2a-7)}{9b-15}](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B%202c%282a-7%29%7D%7B6%283b-5%29%7D%20%3D%20%5Cdfrac%7Bc%282a-7%29%7D%7B9b-15%7D%20)
Substituting,
![y = \dfrac{4(2(2)-7)}{9(3)-15} = \dfrac{ -12}{12} = -1](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B4%282%282%29-7%29%7D%7B9%283%29-15%7D%20%3D%20%5Cdfrac%7B%20-12%7D%7B12%7D%20%3D%20-1)
Answer: -1
Part ii
I'm not sure that one's typed in correctly but I'll solve it as written.
![3-34y + 2a = \dfrac{3b-5}{2c + 1}](https://tex.z-dn.net/?f=3-34y%20%2B%202a%20%3D%20%5Cdfrac%7B3b-5%7D%7B2c%20%2B%201%7D)
![34y = 3+2a-\dfrac{3b-5}{2c + 1}](https://tex.z-dn.net/?f=34y%20%20%3D%203%2B2a-%5Cdfrac%7B3b-5%7D%7B2c%20%2B%201%7D)
![y = \frac 1 {34}\left(3+2a-\dfrac{3b-5}{2c + 1} \right)](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%201%20%7B34%7D%5Cleft%283%2B2a-%5Cdfrac%7B3b-5%7D%7B2c%20%2B%201%7D%20%5Cright%29)
We're not asked to simplify it so I wont. Substituting,
![y = \frac 1 {34}\left(3+2(2)-\dfrac{3(3)-5}{2(4) + 1} \right) = \frac 1 {34}(7-4/9) = \dfrac{59}{306}](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%201%20%7B34%7D%5Cleft%283%2B2%282%29-%5Cdfrac%7B3%283%29-5%7D%7B2%284%29%20%2B%201%7D%20%5Cright%29%20%3D%20%5Cfrac%201%20%7B34%7D%287-4%2F9%29%20%3D%20%5Cdfrac%7B59%7D%7B306%7D)
Answer: 59/306
Answer:
5
Step-by-step explanation:
The clothing store already sold $300 .
They need to sell x jeans to get to $500.
$500 - $300
$200
They’re $200 short of their goal.
A pair of jeans cost $40
Therefore x40 = $200
x = 200/40
x = 5
So ,they need to sell 5 pairs of jeans to hit their $500 target
Answer:0
Step-by-step explanation: 36 divided by 12 equals 3
Slope is rise/run
so, you go up 4 times and run across 3 times, this is a positive slope, so the slope is
slope: 4/3
the y-intercept is the line that passes the y-axis, (0, -5),
y-intercept: -5
put it together
4/3x-5
Slope of a line passing through two given points
= (y2-y1)/(x2-x1)
For m=3, and substituting coordinates,
3=(1-y)/(4-1)
solve for y
1-y=3*3=9
y=1-9=-8
Answer: y=-8